Evaluation of Kynu, Defb2, Camp, and Penk Expression Levels as Psoriasis Marker in the Imiquimod-Induced Psoriasis Model - Zahra Emami; Saeideh Sadat Shobeiri; Razia Khorrami; Navideh Haghnavaz; Mohammad Ali Rezaee; Malihe Moghadam; Safoora Pordel; Mojtaba Sankian (Hindawi Limited, 2024)
Background. Psoriasis is a noncontagious auto-inflammatory chronic skin disease. So far, some of the inflammatory genes were upregulated in mouse model of psoriasis. This study examined changes in skin mRNA expression of L-kynureninase (Kynu), cathelicidin antimicrobial peptide (Camp), beta-defensin 2 (Defb2), and proenkephalin (Penk) in a mouse model of imiquimod-induced psoriasis. Materials and Methods. Tree groups of C57BL/6 female mice were allocated. The imiquimod (IMQ) cream was administered to the mice dorsal skin of the two groups to induce psoriatic inflammation. In the treatment group, IMQ was administered 10 min after hydrogel-containing M7 anti-IL-17A aptamer treatment. Vaseline (Vas) was administered to the negative control group. The psoriatic skin lesions were evaluated based on the psoriasis area severity index (PASI) score, histopathology, and mRNA expression levels of Kynu, Camp, Defb2, and Penk using real-time PCR. In order to assess the systemic response, the spleen and lymph node indexes were also evaluated. Results. The PASI and epidermal thickness scores were 6.01 and 1.96, respectively, in the IMQ group, and they significantly decreased after aptamer administration to 1.15 and 0.90, respectively (P<0.05). Spleen and lymph node indexes showed an increase in the IMQ group, followed by a slight decrease after aptamer treatment (P>0.05). Additionally, the mRNA expression levels of Kynu, Defb2, Camp, and Penk genes in the IMQ-treated region showed a significant 2.70, 4.56, 3.29, and 2.61-fold increase relative to the Vas mice, respectively (P<0.05). The aptamer-treated region exhibited a significant decrease in these gene expression levels (P<0.05). A positive correlation was found between Kynu, Penk, and Camp expression levels and erythema, as well as Camp expression with PASI, scaling, and thickness (P<0.05). Conclusion. According to our results, it seems that Kynu, Camp, and Penk can be considered appropriate markers for the evaluation of psoriasis in IMQ-induced psoriasis. Also, the anti-IL-17 aptamer downregulated these important genes in this mouse model.